FORENSIC LINGUISTICS AS AN ACADEMIC DISCIPLINE - Ashurov Bobir Shakirovich (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores forensic linguistics as an emerging and interdisciplinary academic field that combines principles of linguistics with legal inquiry. It examines the historical development of the discipline, its methodological foundations, and its application in legal contexts such as authorship attribution, courtroom discourse analysis, and interpretation of legal language. The study highlights the significance of forensic linguistics in criminal investigations, legal proceedings, and legislative interpretation. Attention is also given to the pedagogical implications of teaching forensic linguistics in higher education institutions, including curriculum design, skill development, and interdisciplinary collaboration. As the field continues to evolve, the article advocates for broader academic recognition and standardization of training practices, emphasizing its crucial role in promoting justice through linguistic expertise.